Temperature rise test and analysis of high current switchgear in distribution system. Issue 16 (13th February 2019) - Xia, Haotian; Guan, Yonggang; Yu, Zhanqing; Cai, Suxiong; Wang, Xiaorui; Peng, Zhaowei; Gao, Shisen; Huang, Zerong
Abstract : As the load of the power system continues to increase, the capacity of switchgear climbs, resulting in that the overheating problems becoming more serious. In order to realise the monitoring of the temperature of the switchgear, the authors need to conduct a thorough analysis of the temperature rise principle of the switchgear firstly. For the purpose of getting the detailed temperature distribution in the switchgear, a series of temperature rise tests were carried out based on the KYN28A‐12(Z) overhead line switchgear, and the data were analysed and compared in detail to summarise the factors that affect the temperature distribution in the switchgear.